Immigrants' educational credentials leading to employment outcomes: The role played by language skills - Miyar-Busto, María; Mato Díaz, Fco. Javier; Gutiérrez, Rodolfo (Revista Internacional de Organizaciones, 2020)
Transferability of human capital is a key issue in the analysis of immigrants' integration in the destination country, according to both empirical and theoretical literature. In addition to the problem of recognition of immigrants' educational credentials and their lack of social networks, language is highlighted in the literature as a crucial factor regarding human capital transfer. This paper considers the role played by Spanish language skills in the integration of migrants into the labour market in Spain. It takes advantage of the fact that about half of the immigrant population have Spanish as their native language, and of the diversity levels of fluency in Spanish among the remaining immigrants. Using the Labour Force Survey special module on the labour market situation of immigrants (INE 2015), the research has two purposes: first, to measure the direct effect of language skills on employment outcomes; and second, to analyze the complementary vs. substitution hypotheses regarding the interaction between Spanish language skills and educational credentials as determining factors for employment. The results confirm that skill levels in Spanish have a significant role regarding access to employment. Regarding the complementary vs. substitution hypotheses, interesting gender differences appear that confirm the striking contrasts in the Spanish labour market for female and male immigrants. For men, their level of Spanish acts as a complement to their educational qualifications in helping them to obtain employment, but this is not the case for women. However, female immigrant workers seem to obtain higher employment returns on their educational qualifications than men when it comes to avoiding very low-skilled jobs.